2015
DOI: 10.1093/ilar/ilv019
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal Microbiota in Animal Models of Inflammatory Diseases

Abstract: The intestinal microbiota has long been known to play an important role in the maintenance of health. In addition, alterations of the intestinal microbiota have recently been associated with a range of immune-mediated and metabolic disorders. Characterizing the composition and functionality of the intestinal microbiota, unravelling relevant microbe-host interactions, and identifying disease-relevant microbes are therefore currently of major interest in scientific and medical communities. Experimental animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 111 publications
0
29
0
Order By: Relevance
“…This finding is supported further by studies in SAMP1/YitFc mice showing dysfunction within their mesenteric lymph node regulatory T-cell compartment 74 . Studies performed in Tnf ΔARE/+ mice also confirm the importance of host-gut microbiome interactions and dysbiosis in the pathogenesis of CD-like ileitis 75, 76. Schaubeck et al 77 recently showed that germ-free Tnf ΔARE/ + mice were free of intestinal inflammation.…”
Section: Pathogenic Mechanisms Of Crohn’s-like Ileitismentioning
confidence: 79%
“…This finding is supported further by studies in SAMP1/YitFc mice showing dysfunction within their mesenteric lymph node regulatory T-cell compartment 74 . Studies performed in Tnf ΔARE/+ mice also confirm the importance of host-gut microbiome interactions and dysbiosis in the pathogenesis of CD-like ileitis 75, 76. Schaubeck et al 77 recently showed that germ-free Tnf ΔARE/ + mice were free of intestinal inflammation.…”
Section: Pathogenic Mechanisms Of Crohn’s-like Ileitismentioning
confidence: 79%
“…Correlation analysis revealed that the ileal expression of Il1β was positively correlated to the Bacteroides genus although this genus was not significantly affected by the dietary treatments. The usual limitations linked to individual experimental animals also apply to this study 47 . Only one gender and one genetic background were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Gnotobiotic models have been used to reveal causative association between changes in the microbiome in health and disease and to gain functional insights into host-microbe interactions. 77 To address this aspect, a reductionist approach has been adopted to focus the investigation on specific taxa or metabolites of interest, revealing the potential mechanism or mechanisms responsible for the phenomenon observed. One example is the use of IBD-related mouse models monoassociated with a variety of commensal bacteria, including Escherichia coli, Enterococcus faecalis, Bacteroides vulgatus, and Bilophila wadsworthia.…”
Section: Gnotobiotic Model Systems: From Single-strain To Bacterial Cmentioning
confidence: 99%